Antibiotics susceptibility pattern of Methicillin Resistant Staphylococcus aureus isolated from the clinical samples different tertiary care hospitals of Kathmandu - Ghimire, Lata; Banjara, Megha Raj; Pathak, Rakesh; Abdulla, Abdelkodose Mohammed Hussen (Patan Pragya, 2020)
The study was carried out in three different tertiary care hospitals of Kathmandu, Nepal. The objective of the study is to isolate and identify bacteria responsible for the different types of infection and to assess antibiotics susceptibility pattern of methicillin resistant Staphylococcusaureus (MRSA) from the clinical samples in the clinical settings. Various clinical samples as wound, us, bed sore, throat swab, urine and blood were collected from the patients visiting the tertiary care hospitals of Kathamndu. Kirby Bauer disc diffusion test was done to detect antibiotic susceptibility whereas cefoxitin (30mcg) disc was used to detect MRSA. Out of 222 samples, the S. aureus isolatedwas 103(46.4%).Among the S. aureus, 22(21.3%) were methicill in resistant 98.7% of MSSA were sensitive to Meropenem followed by Amikacin and Tetracycline, 97.5% each respectively. MRSA were sensitive to Chloramphenicol (77.2%) followed by Meropenam (72.7%). This study suggests that very few antibiotics are effective against MRSA and therefore there should be rationale use of antibiotics and antibiotics should be prescribed only after susceptibility test.